2007
DOI: 10.1159/000099160
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cerebral Artery A1 Segment Hypoplasia May Contribute to A1 Hypoplasia Syndrome

Abstract: Anterior cerebral artery A1 segment hypoplasia is an uncommon fetal variant of the circle of Willis. The frequency of this congenital variation is 1–13% as derived from angiograms and autopsy reports. Impaired collateral blood flow through the circle of Willis is a recognized risk factor for ischemic stroke. The A1 segment of the anterior cerebral artery is a principal supplier of anterior collateral blood flow. The aim of our study was to determine whether A1 segment hypoplasia may be responsible for acute is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 25 publications
4
50
2
2
Order By: Relevance
“…Studies have shown that up to 13% of the population may have A1 segment hypoplasia, and this is considered a normal variant. 32 We observed a higher incidence in our patients. Our data support and expand the work of others in identifying risk factors for associations with segmental hemangiomas.…”
Section: Hemangioma Segmental Analysissupporting
confidence: 42%
“…Studies have shown that up to 13% of the population may have A1 segment hypoplasia, and this is considered a normal variant. 32 We observed a higher incidence in our patients. Our data support and expand the work of others in identifying risk factors for associations with segmental hemangiomas.…”
Section: Hemangioma Segmental Analysissupporting
confidence: 42%
“…In a prior study, it was thought that the hypoplasia of the ACA A1 segment may be a factor that contributes to acute ischemic stroke, due to compromise of the collateral circulation. When compared with healthy individuals, the anomaly was detected significantly more often in acute ischemic stroke patients 11 . In a study conducted by Shaban et al, hypoplastic and absent ACA A1 were detected in 5.9% of acute ischemic stroke patients, although hypoplastic and absent ACA A1 did not have any effect on vascular distribution, side, or the volume of the infarct 10 .…”
Section: Discussionmentioning
confidence: 91%
“…The frequency of A1 hypoplasia was 1–13%, as derived from angiograms and autopsy reports. To the best of our knowledge, no reports have mentioned the probability of dynamic transformation in A1 segments [4]. …”
Section: Resultsmentioning
confidence: 99%
“…Hoksbergen et al [2 ]explained that among the general population, only approximately 50% have a complete CoW; for others a multitude of possible anatomical variations are present, with absent or hypoplastic vessels being quite common. Schomer et al [3] and Chuang et al [4 ]described that the anatomical variations in the CoW [including the posterior communicating artery (PCoA) hypoplasia and A1 hypoplasia] may preclude collateral compensation, which is regarded as a risk factor for ischemic cerebral infarction. Accordingly, early recognition of such anatomical risk factors has been suggested.…”
Section: Background and Purposementioning
confidence: 99%